A successful full term delivery in a case of robotic assisted insertion of transabdominal cerclage in an obese woman with multiple uterine fibroids - Tan, Y. H.; Durai, S.; Devendra, K.; Ravichandran, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Cervical incompetence is not an uncommon presentation in an obstetric emergency unit. Some of these patients will be managed with a cervical cerclage. While the management of patients presenting with first time cervical incompetence is relatively established, the management of patient with repeated cervical incompetence might require an abdominal cerclage. Abdominal cerclages can be inserted traditionally via laparotomy or via a minimally invasive approach (MIS). We present a case of an obese patient presenting with 3 previous second trimester miscarriages despite 2 cervical cerclage complicated by multiple uterine fibroids who underwent a robotic assisted insertion of transabdominal cerclage (RTAC) pre-pregnancy. She subsequently conceived spontaneously and carried the pregnancy to term and delivered a healthy baby via caesarean section. There have been multiple published studies showing that an MIS approach for abdominal cerclage insertion is safe and viable. Robotic assisted procedures allow for better visualisation and manipulation of tissue especially in patients anticipating a complex procedure. For our patient we feel that a robotic assisted procedure would be more beneficial given her profile and the complexity of her case.